Wellbeing consequences of unemployment and working with a job dissatisfaction in Turkey - Zeynep B. Uğur (International Econometric Review (IER), 2022)
This study aims to shed light on the well-being of unemployed individuals in Turkey by posing two questions. First, are the unemployed unhappier compared to the employed? Second, are the unemployed even unhappier than people unsatisfied with their job? We utilize the Life Satisfaction Survey's individual-level data between the 2004-2020 period. The LSS survey is a nationally representative survey with more than 324,000 observations in 17 years. Firstly, after controlling for household income, the unemployed have considerably lower well-being than the employed. However, compared to employed people who are dissatisfied with their job, the unemployed's well-being is statistically significantly higher. Thus, it appears that unemployment is a negative life event in Turkey as elsewhere, but so is working in a toxic job. Moreover, we find strong gender effects as males and particularly married males suffer more from unemployment. Also, a quarter of the unemployed report that they feel social pressure due to unemployment. These findings suggest that social approval plays some role in the impact of unemployment. Our findings imply that societies similar to Turkey in terms of the labor market would be better off with some unemployment insurance program as it signals to potential quitters that some unemployment is tolerated by society.
Keywords: D91; I31; J64; 330; unemployment; job dissatisfaction; happiness; well-being; Turkey